The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/13625180500035025
|View full text |Cite
|
Sign up to set email alerts
|

Providers' knowledge of, attitude to and practice of emergency contraception

Abstract: One-hundred and fifty-two of the providers stated that they had heard of EC. The correct timing and dose interval of EC were known by 50% of them. The participants held the belief that EC caused abortion (39.4%), and that it was harmful for the fetus (31.1%). Other prejudices were the possibility of increased unprotected sexual intercourse (78.9%) and a tendency for men to give up condom use (75%); female providers were more prejudiced concerning these statements. The providers' tendency towards the provision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 23 publications
4
27
0
1
Order By: Relevance
“…Rather, some respondents worried that use of ECP may discourage regular contraceptive use (17%) or encourage promiscuity (6%). Other studies have found similar concerns among physicians, 7,18,38 although such concerns may be unfounded. 39 It has been shown that compared to clinic access, increased access to ECP via direct pharmacy access or advance provision helps increase ECP use among those in need and allows patients to use it in a more timely manner without changing women's patterns of contraceptive use or sexual risk behaviors.…”
Section: Physicians' Attitudes On Ecp Provision 495mentioning
confidence: 77%
See 3 more Smart Citations
“…Rather, some respondents worried that use of ECP may discourage regular contraceptive use (17%) or encourage promiscuity (6%). Other studies have found similar concerns among physicians, 7,18,38 although such concerns may be unfounded. 39 It has been shown that compared to clinic access, increased access to ECP via direct pharmacy access or advance provision helps increase ECP use among those in need and allows patients to use it in a more timely manner without changing women's patterns of contraceptive use or sexual risk behaviors.…”
Section: Physicians' Attitudes On Ecp Provision 495mentioning
confidence: 77%
“…7,18,28,[35][36][37][38] Few concerns about the safety and efficacy of taking ECP were raised by physicians. Rather, some respondents worried that use of ECP may discourage regular contraceptive use (17%) or encourage promiscuity (6%).…”
Section: Physicians' Attitudes On Ecp Provision 495mentioning
confidence: 99%
See 2 more Smart Citations
“…Although some women consider a method as "abortive" or "abortifacient" if it has an anti-implantation effect [18,28,35], we preferred to use the term "postfertilization" when referring to this mechanism of action. Moreover, although postimplantation effects are considered as abortion in scientific forums [26,[36][37][38], we also avoided the term "abortifacient" to use less value-laden wordings throughout our study.…”
mentioning
confidence: 99%